Strategi Kepala Madrasah Dalam Pengelolaan Konflik di MAN 3 Banda Aceh - Dhin, Cut Nya; Bararah, Isna Wardatul; Daulay, Namiah; Raudhaturrahimah, Raudhaturrahimah (Intelektualita, 2024)
Conflict is a problem that can occur in various organization/institutions, including madrasah. In dealing with conflict between teachers when selecting teachers to serve in the school organizational structure, madrasah principals have several methods for resolving conflicts so that they do not have a negative impact on the school environment. The aims the of this research are 1) to find out the methods of madrasah heads in resolving conflicts at MAN 3 Banda Aceh 2) To find out the obstacles faced by madrasah heads in resolving conflicts at MAN 3 Banda Aceh. The type of research carried out is qualitative, with data collection techniques namely observation, interviews and documentation. The subjects in this research consisted of 3 informants, namely the head of the madrasah, the deputy head of the madrasah for curriculum and 1 homeroom teacher for class X MIA 3. The results of this research show that 1) the method used by the madrasah head to resolve conflicts related to the system for selecting members of the organizational structure is to use 4 methods, namely the method of stimulating conflict, the method of reducing conflict, the method of managing conflict, and the method of conciliation. 2) The obstacles that madrasah heads face in resolving conflicts are misunderstandings and lack of understanding of the rules that occur within the parties involvet in the conflict, resulting in differences of opinion. With the methods used by madrasah heads in resolving conflicts, these problems can be resolved well even though they are not free from obstacles.